Mixed siliciclastic-carbonate sedimentation in an evolving epicontinental sea: Aptian record of marginal marine settings in the interior basins of north-eastern Brazil - Varejao, Filipe G.; Warren, Lucas V. [UNESP]; Simoes, Marcello G. [UNESP]; Buatois, Luis A.; Mangano, M. Gabriela; Bahniuk Rumbelsperger, Anelize M.; Assine, Mario L. [UNESP] (Wiley-Blackwell, 2021)
The Aptian evaporitic transitional sequence (sag phase) of the Brazilian marginal basins records the first connection between the Central and South Atlantic oceans in the equatorial area. During this phase, lacustrine carbonate reservoirs and giant salt deposits developed in the southern basins of Santos and Campos, forming world-class petroleum reservoirs. The sag succession is also well-preserved in the interior rift basins of north-eastern Brazil, where upper Aptian strata are represented by a continuous section. This contribution presents an interpretation of the evolution of a third-order depositional sequence comprising lacustrine limestones, marine siliciclastic facies and evaporite deposits of the intracontinental Araripe Basin. The Lowstand Systems Tract is characterized by fluvial deposits filling accommodation generated during the syn-rift phase. The overlying deposits comprise marine facies with preservation of dinoflagellates and marine ichnotaxa, evidencing marine deposition in bayhead delta settings. The transgressive surface is represented by limestones, including the Konservat-Lagerstatte laminites, onlapping the basement rocks. Above, tide-dominated bay deposits with distinct subtidal, intertidal and supratidal portions are recorded. The Maximum Flooding Surface is a dark shale below foreshore to shoreface facies, marking the beginning of the Highstand Systems Tract, culminating with deposition of evaporites (gypsum and anhydrite). The stratigraphic architecture and palaeocurrents measured in different facies associations suggest that marine waters reached the basin from the south. The data unequivocally records late Aptian marine ingressions of an incipient South Atlantic Ocean over the interior basins of north-eastern Brazil, while lacustrine conditions were still prevailing in the Pre-Salt sag units of the Santos and Campos basins.
Keywords: Aptian; Cretaceous Konservat– Lagerstä tte; epicontinental marine ingression; mixed carbonate– siliciclastic system; Pre‐ Salt analogue